Production, characterization and properties of polysaccharide depolymerizing enzymes from a strain of Curvularia inaequalis - Gomes, E. [UNESP]; Iembo, T. [UNESP]; Da Silva, R. [UNESP] (Springer Nature, 2001)
Xylanase, β-glucosidase, β-xylosidase, endoglucanase and polygalacturonase production from Curvularia inaequalis was carried out by means of solid-state and submerged fermentation using different carbon sources. β-Glucosidase, β-xylosidase, polygalacturonase and xylanase produced by the microorganisms were characterized. β-Glucosidase presented optimum activity at pH 5.5 whereas xylanase, polygalacturonase and β-xylosidase activities were optimal at pH 5.0. Maximal activity of β-glucosidase was determined at 60°C, β-xylosidase at 70°C, and polygalacturonase and xylanase at 55°C. These enzymes were stable at acidic to neutral pH and at 40-45°C. The crude enzyme solution was studied for the hydrolysis of agricultural residues.
Keywords: glycosidase; polysaccharide; Ascomycetes; crop; culture medium; enzymology; evaluation; fermentation; growth, development and aging; hydrolysis; metabolism; pH; temperature; Ascomycota; Crops, Agricultural; Culture Media; Fermentation; Glycoside Hydrolases; Hydrogen-Ion Concentration; Hydrolysis; Polysaccharides; Temperature